OBJECTIVITY AND GRAPHIC FORMALIZATION OF MODERN PROJECT VISUALIZATION IN DESIGN - Яковлєв, М. І.; Бердинських, С. О.; Колосніченко, О. В.; Пашкевич, К. Л. (Art and Design, 2023)
Purpose. The aim of the study is to identify and systematize the main visual means of presenting the design idea in modern design practice, to establish their role in conveying the objective and emotional properties of the presented object. Methodology. The research used the analysis of information sources in the field of application of the latest means of visualization of creative projects, the analysis of the portfolio of contemporary designers and CG artists; structural and systemic analysis; synthesis of research results. Results. Design graphics in contemporary design practice plays the role of the main means to prove the value of a design idea, revealing its most essential aspects. The evolution of visualization tools in design has happened recently due to the rapid development of digital and information technologies, particularly in the field of 3d modeling, with the simultaneous functioning of traditional imaging tools and methods. It is defined that the most common means of visualization today is an objective image, which is built on the principles of physical correctness, and which carries the expressive principles of artistic photography. Also the images constructed using the principles of conventional transfer of object properties, which differ in their effectiveness at building a visual expression, are gaining popularity compared to other means. They include forms such as vector linear images, sketching, non-photorealistic visualization, digital collage. This research has established priorities for using each of these tools in representative tasks. Scientific Novelty. For the first time in the research, modern tools nomenclature for presenting design projects have been expanded and systematized, their role and functional properties have been identified. The practical significance of the obtained results lies in the possibility of their application in design practice, in the educational process of preparing specialists in the artistic and creative fields, and in further research in art history, cultural studies, architecture, and design.